2014
DOI: 10.15549/jeecar.v1i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Investment Risks and Insurance in the Gold Market

Abstract: In this article we investigated the causes and features of investment risks in the gold market, studied the components of investment risks in this market, and analyzed the main methods of insuring those investment risks. In addition, we presented the methods and financial investment instruments used in gold operations and provided the conceptual analyses of investment risk in the gold market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research work of many scientists is devoted to studying industry-specific features of investment risk management. Megits et al [8] identified the causes and characteristics of investment risks in the base material sector using the example of the gold mining market, studied the investment risk components, analyzed the principal techniques of insuring them, and conducted a conceptual analysis of the investment risk in this industry. Botín, Guzmán and Smith [9] proposed an approach based on assessing the investment risk at every stage in the life cycle of a mining project, from exploration to mine closure, while risk management is carried out as part of a phased process of value added optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The research work of many scientists is devoted to studying industry-specific features of investment risk management. Megits et al [8] identified the causes and characteristics of investment risks in the base material sector using the example of the gold mining market, studied the investment risk components, analyzed the principal techniques of insuring them, and conducted a conceptual analysis of the investment risk in this industry. Botín, Guzmán and Smith [9] proposed an approach based on assessing the investment risk at every stage in the life cycle of a mining project, from exploration to mine closure, while risk management is carried out as part of a phased process of value added optimization.…”
Section: Introductionmentioning
confidence: 99%